IMPROVING ACTIVITY AND KKM ACHIEVEMENT THROUGH PROBLEM BASED LEARNING MODELS ON SOCIAL PROBLEMS LEARNING MATERIALS AT CLASS XI SOCIAL 5, 1ST SEMESTER, SUKABUMI 4TH SENIOR HIGH SCHOOL ACADEMIC YEAR 2020/2021: UPAYA MENINGKATKAN KEAKTIFAN DAN PENCAPAIAN KKM MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI PERMASALAHAN SOSIAL KELAS XI IPS 5 SEMESTER I SMA NEGERI 4 SUKABUMI TAHUN AJARAN 2020/2021 - Farhan Firdaus (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
This study aims to increase the activeness and achievement of the Minimum Completeness Criteria (KKM) on social problems materials using a problem-based learning model in class XI Social 5 Sukabumi 4th Senior High School. Classroom action research was conduct in two cycles of action. Each cycle consists of several stages, there is planning, implementing actions, observing and reflecting. Cycle I discusses the factors that cause social problems and cycle II discusses the social problem theory. The research subjects of class XI Social 5 Sukabumi 4th Senior High School in the 2020/2021 academic year consisted of 32 students. Data collection was carried out by observation, interviews and documentation. Based on the results of observations, increase of the KKM achievement can be seen from the pretest and posttest activities done by students. The results obtained showed an increase in learning activeness in the cycle 1 by 89.9%, increasing to 91.2% in the cycle 2. The results obtained showed an increase in the KKM achievement results in Cycle I by 36% with B predicate, 64% with C predicate and there is no score that reached A predicate. It is different in cycle II there was able to obtain 13 % score with A predicate, 43% predicate B, and 43% the score with predicate C. The results of this study indicate that applying a problem-based learning model can increase activeness and the KKM achievement in sociology learning in class XI Social 5 Sukabumi 4th Senior High School in the 2020/2021 academic year